Reverse-hydroformylation: a missing reaction explored - Nandakumar, Avanashiappan; Sahoo, Manoj Kumar; Balaraman, Ekambaram (Organic Chemistry Frontiers, 2015)
Recent progress in transition-metal catalysed acceptor- and acceptorless-reverse hydroformylation of aldehydes for the conversion of olefins has been discussed. The aldehyde feedstock serves as a source for production of syngas and valuable alkenes.